Portal hypertension - Reinus, John (Henry Stewart Talks, 2011)
Portal hypertension causes regional circulatory derangements that result in extra- and intra-vascular volume overload and organ dysfunction, Vascular tone is mediated by autonomic input and chemical mediators many of which are released by local vascular endothelium, Intrahepatic portal hypertension develops as a result of anatomic changes in the cirrhotic liver that cause sinusoidal narrowing and loss of compliance, Reflex SMA vasoconstriction and portosystemic shunting up-regulate VEGF eNOS and iNOS with resultant vasodilation, There is secondary: ADH secretion with retention of free water; renal salt retention; renal afferent arteriolar vasoconstriction, Affected individuals develop progressive volume overload with associated afterload reduction and increases in cardiac output (hyperdynamic circulation), Fluid is forced off the surface of the liver and accumulates in the abdominal cavity as ascites, Blood is shunted around the liver through latent venous connections that become varices, Renal function is impaired (hepatorenal syndrome), Volume overload may cause secondary pulmonary hypertension, Affected individuals may also develop primary pulmonary hypertension due to anatomic alterations of pulmonary microvasculature (porto-pulmonary hypertension), The ability of the heart to respond to stress is impaired, Patients develop intrapulmonary shunts that cause hypoxemia (hepatopulmonary syndrome), The only real remedy for these problems is orthotopic liver transplantation
Reviewed at 2018/06/15